Linguistic Interdependence Hypothesis: Does the Positive Transfer in Writing Skill Occur in Lower Level Students? - Beby Maharani Masyitha; Utami Widiati; Ekaning Dewanti Laksmi (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: Language transfer always becomes an interesting topic to discuss in SLA. From the two types of language transfer take place in the process of language learning, this research aims to investigate the positive transfer occurs in junior high school students' writing skill. The two languages to be involved in this research, Indonesian as L1 and English as L2. The analysis of the positive transfer within writing skill in this research is carried out under the theory of 'Linguistic Interdependence Hypothesis' proposed by Cummins. Correlational research design is employed to analyze the correlation between the students' L1 (Indonesian) writing ability and L2 (English) writing ability. The analysis result shows that the positive transfer in students' writing does not exist. This happens due to the lack of exposure that the students have in practicing L2 (English) writing. Abstrak: Transfer bahasa selalu menjadi topik yang menarik untuk dibicarakan dalam pemerolehan bahasa kedua. Dari dua jenis transfer bahasa yang terjadi dalam proses pembelajaran bahasa. Penelitian ini bertujuan untuk menginvestigasi transfer positif yang terjadi dalam keterampilan menulis siswa SMP. Ada dua bahasa yang dilibatkan dalam penelitian ini, yaitu bahasa bahasa Indonesia dan bahasa Inggris. Analisis transfer positif dalam keterampilan menulis pada penelitian ini mengacu pada teori 'Linguistic Interdependence Hypothesis' yang digagas oleh Cummins. Penelitian ini menggunakan metode korelasional untuk menganalisis korelasi kemampuan menulis siswa dalam bahasa Indonesia dan bahasa Inggris. Hasil analisis menunjukkan bahwa tidak ada transfer positif yang terjadi dalam tulisan siswa. Hal ini terjadi karena kurangnya pajanan yang diterima siswa untuk mengasah keterampilan menulis dalam bahasa Inggris.